Implementasi Sistem Manajemen Antrian Pendaftaran Pasien Pada Rumah Sakit Islam Malahayati Untuk Mengurangi Waktu Tunggu - Piliang, Dinara Sarvina; Siregar, Silviana Ayu; Siahaan, Ahmad Taufik Al Afkari (CV. ITTC INDONESIA, 2023)
To reduce patient waiting time, this research explores and implements a patient registration queue management system at the Malahayati Islamic Hospital. The method uses a research and development (RnD) approach to design, develop, and implement an efficient system for managing the patient registration process. This research involves preparation, design, development, evaluation and revision stages. It collects data through direct observation, historical analysis of wait times, and patient satisfaction questionnaires to evaluate the impact of system implementation on patient wait times, registration efficiency, and patient satisfaction. The research results show that the implementation of the queue management system has succeeded in reducing patient waiting time and increasing the efficiency of the registration process. Patient satisfaction assessments also showed that these changes were well received. The results show that the implementation of the patient registration queue management system at Malahayati Islamic Hospital improves health services and reduces patient waiting time. This research provides a basis for hospitals and other healthcare institutions to consider implementing this technology in more efficient administrative processes and increasing patient satisfaction.